1999
DOI: 10.1002/(sici)1521-4184(19999)332:9<317::aid-ardp317>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiproliferative Activity of Novel 3-(Indazol-3-yl)-quinazolin-4(3H)-one and 3-(Indazol-3-yl)-benzotriazin-4(3H)-one Derivatives

Abstract: Several new 3‐(indazol‐3‐yl)‐quinazolin‐4(3H)‐one and 3‐(indazol‐3‐yl)‐benzotriazin‐4(3H)‐one derivatives 5 and 6 were synthesized and tested for their in vitro antiproliferative activity against Raji, K562, and K562‐R cell lines. The pharmacological screening showed that some 2, 6, or 7‐substituted quinazolinones 5 posses a significant antiproliferative activity, with a percentage growth inhibition ranging from 44.8% to 100% at 50 μM, which was higher than that showed by the unsubstituted derivative 5a previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Daidone et al (2004) prepared several triazenoindazoles and tested them for their antiproliferative activities against K562, HL60, L1210, and MCF7 cell lines out of which 3-(3,3-diethyltriazeno)-5-chloroindazole (33) showed potent antiproliferative activity. Raffa et al (1999) synthesized several new 3-(indazol-3-yl)-quinazolin-4-(3H)-one (34) and 3-(indazol-3-yl)benzotriazin-4-(3H)-one (35) derivatives and tested for their in vitro antiproliferative activity against Raji, K562, and K562-R cell lines. The pharmacological screening showed that some of the 2, 6, or 7-substituted 3-(indazol-3-yl)quinazolinones possessed a significant antiproliferative activity.…”
Section: Indazoles As Antimicrobial Agentsmentioning
confidence: 99%
“…Daidone et al (2004) prepared several triazenoindazoles and tested them for their antiproliferative activities against K562, HL60, L1210, and MCF7 cell lines out of which 3-(3,3-diethyltriazeno)-5-chloroindazole (33) showed potent antiproliferative activity. Raffa et al (1999) synthesized several new 3-(indazol-3-yl)-quinazolin-4-(3H)-one (34) and 3-(indazol-3-yl)benzotriazin-4-(3H)-one (35) derivatives and tested for their in vitro antiproliferative activity against Raji, K562, and K562-R cell lines. The pharmacological screening showed that some of the 2, 6, or 7-substituted 3-(indazol-3-yl)quinazolinones possessed a significant antiproliferative activity.…”
Section: Indazoles As Antimicrobial Agentsmentioning
confidence: 99%
“…This molecules which based on the quinazolin-4-one ring were reported as interesting pharmacological activities, 6 including anticonvulsant, antibacterial, anti tumor, 7 analgesic, 8 antiinflammatory, 9 and anti-diabetic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the methylation/ethylation was observed only with the orthobenzoates, while the unethylated 3-indazolyl-4(3H)-quinazolinones were obtained if triethyl orthoformate, triethyl orthoacetate or triethyl orthopropionate were used. 8 The possible reason of such result was likely due to the higher boiling points of orthobenzoates with respect to the other orthoesters (Table 1). In order to verify this statement, a mixture of 3-(2-aminobenzamido)indazole 1a in triethyl orthobenzoate 2f was left at 160°C for 5 hours (Scheme 1) giving the 3-(1H-indazol-3-yl)-2-phenylquinazolin-4(3H)-one 3a as the main product (20% yield) together with the starting material, instead of the N-ethyl derivative 3f (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%